Evaluation of the Success Nutrition Fulfillment Campaigns Through Diet in People with Autistic Disabilities Based on Prototyping Tasks in Design Thinking - Silfiatul Ulumiyah; Mochamad Chandra Saputra; Retno Indah Rokhmawati (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
Consideration of people, problems, and context is part of the design thinking approach to problem solving. Redefining complicated problems effectively can benefit greatly from this method. Specifically in this study, the development of the nutrition fulfillment application program for autistic children. The calculation of the percentage of test participants who successfully completed the task was 94.3%. The prototype provides high effectiveness based on the assigned task related to the daily diet food menus for autism. The results of the evaluation of the efficiency aspect present a value of 0.085 goals/sec which means that test participants completed 1 task in about 11.76 seconds and is more efficient than the manual process. The result of satisfaction evaluation based on SUS shows that average of the result of the questionnaire is 72 from 100 means that the user easily operates the prototype.